Factors Affecting Users’ Behavioural Intention Towards Touch ‘N Go E-Wallet in Malaysia - Gaik Lynn Yeoh (International Journal of Applied Business and International Management, 2022)
As the outbreak of COVID-19 progresses to the endemic stage, Malaysians are getting used to the norm of going cashless to purchase goods and services, whether through online platforms or physical stores to reduce contact with others. Hence, Touch ‘n Go has garnered a significant number of users since the pandemic. While it is convenient for users to make payments; concurrently, it may pose a risk with many factors that may influence the users’ loyalty to continue using online transactions. This paper aims to study the behavioural intention of the users’ loyalty to Touch ‘n Go E-wallet, given different payment options which are online transaction or physical payment. We investigate whether perceived usefulness, ease-of-use, trust, security, and social influence will affect the users’ loyalty to continue using the application. Responses collected from 150 Touch ‘n Go E-wallet users’ through an online survey, whereby the data will be analysed using SPSS. Implications and recommendations to enhance users’ loyalty, as well as increase acceptance to digital transformation, were presented. Keywords: Behavioural intention, Digital wallet, Perceived ease-of-use, Perceived security, Perceived trust, Perceived usefulness, Social influence, Touch ‘n Go.